Characterization Of Ancient Glass Excavated In Enez (Ancient Ainos) Turkey By Combined Instrumental Neutron Activation Analysis And Fourier Transform Infrared Spectrometry Techniques - Mukhamedshina, Nuranya M.; Mirsagatova, A. Adiba; Başaran, Sait; Çakan, Banu; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Pergamon-Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, England, 2012)
Ancient glass fragments excavated in the archaeological district Enez (Ancient Ainos)-Turkey were investigated by combined Instrumental Neutron Activation Analysis (INAA) and Fourier Transform Infrared (FTIR) spectrometry techniques. Multi-elemental contents of 15 glass fragments that belong to Hellenistic, Roman, Byzantine, and Ottoman Periods, were determined by INAA. The concentrations of twenty six elements (Na, K, Ca, Sc, Cr, Mn, Fe, Co, Cu, Zn, As, Rb, Sr, Sb, Cs, Ba, Ce, Sm, Eu, Tb, Yb, Lu, Hf, Ta, Au and Th), which might be present in the samples as flux, stabilizers, colorants or opacifiers, and impurities, were examined. Chemometric treatment of the INAA data was performed and principle component analysis revealed presence of 3 distinct groups. The thermal history of the glass samples was determined by FTIR spectrometry. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ancient glass; infrared spectrometry; neutron activation analysis; principle component analysis; aluminosilicate glasses; fictive temperature; medieval glass; spectroscopy; raman; INAA; spectra; SIO2; IR; antik cam; infrared spektrometri; nötron aktivasyon analizi; ana bileşen analizi; alüminosilikat camları; kurgusal sıcaklık; ortaçağ cam; spektroskopi; spektrum